ДЕЯКІ СТЕРЕОТИПИ СВІТОГЛЯДУ ЧЕКІСТІВ ПІД ЧАС “ВЕЛИКОГО ТЕРОРУ” (193701938 РР.) (Zaporizhzhia Historical Review, 2021)
The article is dedicated to studying some widespread worldview stereotypes of People’s Commissariat of Internal Affairs (PCIA) officials during “Great Terror” in 1937-1938s. Typical Chekist image and his worldview focus is shown. Conclusion is made that the image was constituent of state Party officials and population consciousness manipulation policy in 1930s.